2023
DOI: 10.3389/fpsyg.2023.1036624
|View full text |Cite
|
Sign up to set email alerts
|

Are you more risk-seeking when helping others? Effects of situational urgency and peer presence on prosocial risky behavior

Abstract: IntroductionProsocial risky behavior (PRB) proposes that individuals take risks for others’ benefits or social welfare, and that this may involve trade-offs between risk and social preferences. However, little is known about the underlying cognitive mechanisms of risk-seeking or aversion during PRB.MethodsThis study adopted the dilemma-priming paradigm to examine the interaction between the risk levels of personal cost and situational urgency on PRB (Experiment 1, N  = 88), and it further uncovered the modulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…These result revealed that when an individual experienced risky dilemmas made them more compassionate for strangers [10] in an urgent and non-urgent situations. Furthermore, individuals demonstrated evident risk-taking behavior when helping others.…”
Section: Table III Test Of Significant Relationship Between Empathic ...mentioning
confidence: 89%
“…These result revealed that when an individual experienced risky dilemmas made them more compassionate for strangers [10] in an urgent and non-urgent situations. Furthermore, individuals demonstrated evident risk-taking behavior when helping others.…”
Section: Table III Test Of Significant Relationship Between Empathic ...mentioning
confidence: 89%